Designing a Pictogram-Based Visual Language Tool for Self-Determination - Spencer, Herbert; Mortensen Steagall, Marcos (Translator) (School of Art and Design, AUT, 2024)
This presentation focuses on a doctoral research project aimed at developing a pictogram-based visual language system to support individuals with complex communication needs (CCN) in Chile and Aotearoa New Zealand. The project seeks to enhance the self-determination and independence of adults with CCN by creating a universally accessible tool that promotes self-expression. The research employs a practice-based methodology, combining theoretical frameworks in augmentative communication with practical design and testing processes. It builds on existing research, such as the PICTOS project in Chile, which has advanced accessibility in public services through the use of pictograms. This project aims to extend such applications into a cohesive visual language system that enables improved decision-making and autonomy for users with CCN. The research design includes co-creation workshops with stakeholders, iterative prototyping, and extensive field testing to ensure that the tool is responsive to the real-world needs and challenges faced by individuals with CCN. Accessible communication methods, such as easy-to-read documents and visual aids, are integrated into the research process to ensure participant comprehension. The project follows a mixed-methods approach, collecting both quantitative and qualitative data to evaluate the tool’s effectiveness, with self-determination measured using standardised instruments alongside interviews, testimonials, and focus groups. Funded by a FONDEF IDEA project grant in Chile and supplemented by scholarships, the research contributes to the fields of augmentative communication and visual language systems, with the ultimate goal of improving communication accessibility for underserved populations in both Chile and Aotearoa New Zealand.